Exploration of the Transcriptional Landscape of ALPPS Reveals the Pathways of Accelerated Liver Regeneration - Borger, Pieter; Schneider, Marcel; Frick, Lukas; Langiewicz, Magda; Sorokin, Maksim; Buzdin, Anton; Kachaylo, Ekaterina; Graf, Rolf; Humar, Bostjan; Clavien, Pierre-Alain (Frontiers in Oncology, 2019)
ALPPS (associating liver partition and portal vein ligation for staged hepatectomy), a novel 2-staged hepatectomy, dramatically accelerates liver regeneration and thus enables extensive liver tumour resection. The signalling networks underlying the ALPPS-induced accelerated regeneration process are largely unknown. Here, we comprehensively categorise and quantify the involved intracellular signalling pathways (ISPs) that demarcate ALPPS from standard hepatectomy (68% resection model). We performed transcriptome profiling of liver tissues from an ALPPS mouse model, standard hepatectomy (68% model), and additional control surgeries (sham, PVL and Tx), and from human liver biopsies (n=5) taken after ALPPS surgery. Oncofinder computational tools, covering 378 ISPs, were used to quantify ISP activity. Relative to standard hepatectomy, ALPPS surgery induced an earlier cell cycle entrance associated with increased activity of IGF1R, ILK and IL10 signalling (all p<0.05) and decreased IFN signalling (p<0.05). PAK- and ILK-associated signalling pathways were activated at an earlier time point and may therefore explain the ALPPS-induced accelerated liver regeneration (p<0.001). Cluster ontology analysis identified these pathways to control cell growth and proliferation, inflammatory response, and hypoxia-related processes. The same pathways and biological responses were recovered in human liver biopsies designating that our murine ALPPS model—despite differences—reflects ALPPS-induced accelerated liver regeneration in humans.